Applying Chi-Square Test In Measuring The Significance Of The Occurrence Of French Synonym In Corpus Data - Savitri, Weddha; Beratha, Ni Luh Sutjiati; Sudipa, I Nengah; Rajeg, I Made (International Journal of Linguistics and Discourse Analytics, 2024)
This paper explains how to apply the significance test of a synonym set in French to its appearance in a data corpus. The chi-square significance test is a procedure that can be used to test the significance of quantitative data statistically. The object of this research is a series of adjective synonyms with the core meaning 'extraordinary' in French. This research uses Leipzig corpora collection as data source, and AntConc (version 4.2.0) as a tool used in searching for the frequency of occurrence of each synonymous word in the news and website data corpus. The results of the significance test show that distributions differences between the real frequency of occurrence and the expected frequency of occurrence of synonymous words in the data corpus can be considered as not just a coincidence. With a p value < 0.001, it can be concluded that there is a significant relationship between the differences in the distribution of each adjective in different types of data corpus